Rancang Bangun Sistem Presensi Pegawai NON ASN Berbasis Website Pada Unit Pelayanan Pengumutan Pajak Daerah Uppd Tanah Wilayah Tanah Abang Jakarta Pusat - Andika Bayu Hasta Yanto; Novalian Ramuchdani; Ade Setiawan; Rifky Permana; Andry Maulana; Ahmad Fauzi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Management of non-ASN personnel attendance data is still carried out by entering the data into Microsoft Excel or Google Spreadsheet which has been provided by the office, then printing it into an attendance card is done by writing and archiving is saved via hardcopy which is also still not optimal. Therefore, mistakes often occur in the process of storing attendance data and not having back up data for honorary employees. From this gal, the author created a system that can help employees to take attendance and record attendance. By using a system development method, namely Software Development Life Cycle (SDLC) using the waterfall model, the author carried out this research to create a system that can be useful. With an employee attendance system, it can make it easier to record absences in a neater and more systematic manner for non-ASN employees. Non-ASN employees prefer to have a summary of their respective absence data so that if there is an error in salary payment, they can attach a summary of their absence